Constructing undergraduate psychology curricula promoting authentic learning and assessment in the teaching of psychology - Mayo, Joseph A. (American Psychological Association, 2010)
"Although courses differ widely across undergraduate institutions, dedicated psychology educators at all academic levels share an interest in uncovering optimal teaching practices. To aid the process of pedagogical discovery, this book addresses three contemporary concerns of psychology teachers and links these ideas to the first five learning goals and outcomes discussed in the American Psychological Associations (APAs; 2007) Guidelines for the Undergraduate Psychology Major: (a) knowledge base of psychology, (b) research methods in psychology, (c) critical thinking skills in psychology, (d) application of psychology, and (e) values in psychology. Within the broad framework of a constructivist educational perspective that promotes active and enduring learning, this book affords undergraduate psychology teachers opportunities to (a) align course content with APA-endorsed student learning outcomes, (b) integrate class-tested instructional strategies with authentic or "real-world" learning and assessment tools designed to foster higher order thinking, and (c) assess students understandings of course content along a developmental continuum that gauges academic progress from the introductory psychology course through receipt of the baccalaureate degree. This book is not meant to be prescriptive. Rather, it is intended as an advisory instructional resource to provide a general framework from which to approach undergraduate psychology curricula-- one that permits maximum flexibility in relation to faculty, student, and institutional differences"--Foreword. (PsycINFO Database Record (c) 2010 APA, all rights reserved)